Aligning pay increases with psychological ownership: A value chain perspective on employee compensation - Grasser, Robert A.; Martin, Patrick R.; Stikeleather, Bryan (Accounting, Organizations and Society, 2026)
Employers often give employees general pay increases that are not tied to individual performance. These pay increases can either be unconditional fixed pay raises such as cost-of-living adjustments or be tied to risky firm-level measures of performance (e.g., profit-sharing). We use two experiments and a survey to investigate how employees' position in the firm's value chain affects their psychological ownership of the firm and subsequently their preferences for different types of pay increases. We find theory-consistent evidence that employees exhibit higher levels of psychological ownership of their organization when they add value to their firm's products and services directly (i.e., are primary workers who produce goods or services) rather than indirectly (i.e., are support workers such as janitorial or safety staff) and that this in turn increases their preferences for a profit-sharing pay increase relative to an unconditional pay increase. We discuss the implications of adopting a “value chain” perspective when designing employee compensation packages.